Transesterification of Yellow Oleander seed oil, its utilization as biodiesel and performance evaluation. Issue 4 (April 2022) - Bhattacharyya, Subhrajyoti
Abstract: Traditional fossil fuels are our primary source of energy, but due to the rapidly increasing human population and their never-ending demands is diminishing the petroleum reserves quickly as they are in a limited stock inside the earth and the pollution caused by fossil fuels is a matter of great concern, so we need an alternative safe, clean & green source of fuel. Biodiesel is attracting everyone's eyes as an alternative and renewable energy. In this study, feedstock was prepared, and the oil was extracted from Thevetia peruviana seeds and transesterified. The transesterified biodiesel oil's physical and chemical properties were determined and compared with the universal standard values. The GC-MS and FTIR were used to determine fatty acids and esters present in the transesterified biodiesel oil. The novelty in this study is that the use of this novel method which produces an outstanding quality of Biodiesel oil, the methods employed in the analysis and determination of physicochemical properties and the chemical structure of the Thevetia Peruviana Biodiesel Oil and comparing these properties to check its usability as Biodiesel and the new type of non-edible oilseeds (Yellow Oleander) seeds used as a source of the biodiesel oil. Graphical abstract: Image 1 Highlights: Yellow Oleander seeds were collected, and their oil was extracted. The oil was transesterified, and its physicochemical properties were determined. The oil properties were compared with the properties of Biodiesel, Diesel. The oil properties were compared with the properties of B10, B20. Abstract : Biodiesel, Transesterification, Yellow Oleander seed oil, Soxhlet extraction method, GC-MS, FTIR.